Cloning of cDNAs that encode human mast cell carboxypeptidase A, and comparison of the protein with mouse mast cell carboxypeptidase A and rat pancreatic carboxypeptidases. - Reynolds, D S (1989)
Human skin and lung mast cells and rodent peritoneal mast cells contain a carboxypeptidase in their secretory granules. We have screened human lung cDNA libraries with a mouse mast cell carboxypeptidase A (MC-CPA) cDNA probe to isolate a near-full-length cDNA that encodes human MC-CPA. The 5' end of the human MC-CPA transcript was defined by direct mRNA sequencing and by isolation and partial sequencing of the human MC-CPA gene. Human MC-CPA is predicted to be translated as a 417 amino acid preproenzyme which includes a 15 amino acid signal peptide and a 94 amino acid activation peptide. The mature human MC-CPA enzyme has a predicted size of 36.1 kDa, a net positive charge of 16 at neutral pH, and 86% amino acid sequence identity with mouse MC-CPA. DNA blot analyses showed that human MC-CPA mRNA is transcribed from a single locus in the human genome. Comparison of the human MC-CPA with mouse MC-CPA and with three rat pancreatic carboxypeptidases shows that these enzymes are encoded by distinct but homologous genes.